The Role of Voice in Virtual Reality Interactive Narratives - Haahr, Mads (My University, 2024)
Providing enough information to allow the VR player to self-identify is an important factor in their immersion into a virtual world. The sensory information being provided to the player’s eyes and ears through the headset must support the suspension of disbelief and telepresence into the virtual world. Given sound’s easily realized potential for diegetic ambiguity and its influence on presence as immersion, the aim of this paper is to explore the role of disembodied voice in VR interactive narratives and its effect on presence through self-identification. We start by analyzing the shift of focalization in the film Saving Private Ryan, the trans-diegetic narration in the game StarCraft II, and the address of the player in the game Call of Duty. We then contribute with close readings of two VR productions, The Last Goodbye and The Book of Distance, in terms of the use of second-person voice and interactivity as well as an analysis of the resulting levels of self-identification. A further contribution is a Twine interactive narrative that demonstrates some of the key concepts discussed in the paper. We conclude that future empirical work should explore the impact of second-person voice and interaction on the resultant self-identification and immersion.
Keywords: virtual reality, second-person, immersion, interactive narrative; Creative Technologies